ПРОЦЕДУРИ ВЗАЄМОДІЇ ОРГАНІВ МІСЦЕВОГО САМОВРЯДУВАННЯ З ПРАВООХОРОННИМИ ОРГАНАМИ - Бурбика, Віталій Олександрович (SUPREMANCE OF LAW, 2017)
The article, based on an analysis of scientific views of scientists, the theoretical approaches to the interpretation of the concept of “procedure” and “administrative procedure”. Emphasized that most acts procedure of interaction of these bodies is described only superficially proved that important to develop specific procedures of interaction of these bodies, and consolidate them in the current legislation, because in this case the interaction of these bodies will be more effective and goal their joint activities will become more real and quick.